Survivable Restructuring of Vegetable Distribution and Wholesale Markets in Western China - Zhao, Liming (Springer, 2015)
The subject of this book is to reveal the formation process of circulation structure centering on vegetable wholesale market in western cities of China. The data are mainly from the interview and survey on farmers, vegetable wholesalers and retailers and operators of vegetable wholesale markets. The findings of the research show that the large vegetable production bases in eastern economically developed regions place stress on local vegetable circulation through wholesale markets, which results in the change in circulation channel in vegetable wholesale markets in western cities, namely, the circulation channel focusing on local vegetable has been shifted to non-local vegetables. The readers will get inspiration from the book that circulation channels have boasted a significance to the small vegetable bases surrounding the cities.